(untitled) (Medical Forum Monthly, 2024)
Objective: The goal of this study was primarily to test the diagnostic utility of immunohistochemical stains p63 and cytokeratin 8/18 in the differentiation of malignant and non malignant lesions to prevent unnecessarily surgical intervention . Study Design: Comparative / cross sectional study. Place and Duration of Study: This study was conducted at the Department of Pathology, Dow University of Health Sciences, Karachi from 1 January 2015 to 31 January 2016. Materials and Methods: Immunohistochemical stains p63 and cytokertin 8/18 were performed on 182 cases on needle core breast biopsies. Patients' name, age, histology numbers, diagnosis. type of tumor,grade of tumor, and expression of p63 and cytokeratin 8/18 were recorded with special emphasis on myoepithelial layer integrity and foci of invasion. Results: Total number of cases were 182. Mean age was 42 years( 27-70),Malignant lesions113(62.1%),Benign lesions 18(9.8%), Fibroepithelial lesion10(5.5%).Papillary lesions4(2.2%),Benign breast tissue37(20.3%). Most common malignant lesion was infiltrating ductal carcinoma 98(53.8%)followed by infiltrating lobular carcinoma 3(1.6%), mucinous carcinoma 2 (1.1%)& ductal carcinoma in situ were 10(5.5%). Benign lesions were peri ductal mastitis/chronic granulomatous mastitis 10(5.5%),sclerosing adenosis 3(1.6%)and ductal hyperplasia 5(2.7%). Conclusion: The responsibility of the pathologist is to provide accurate diagnosis thus placing the patient in the appropriate therapeutic algorithm.